SIFAT MEKANIK BIOKOMPOSIT POLIPROPILENA DAUR ULANG MENGGUNAKAN SERAT ALANG-ALANG (Imperata cylindrica) - Sunardi, Sunardi; Fitriana, Iin Noor; Wianto, Totok (Jurnal Riset Industri Hasil Hutan, 2013)
Synthesized and characterization of biocomposites from recycle polypropylene  with alang-alang (Imperata cylindrica) as reinforcement have been done. Biocomposites was made by mixing biomass with recycle polypropylene in various amount of alang-alang  (0%, 10%, 20%, and 30%). The materials were characterized by FTIR spectroscopy (Fourier Transform Infrared) and SEM (Scanning Electron Microscopy). The physical and mechanical properties of the biocomposite materials were tested in material density, water content, porosity, modulus of elasticity (MOE) and modulus of rupture (MOR). The results was showed that the biocomposites with  alang-alang as reonforcement have better properties than their constituent materials. Biocomposites with 10% of alang-alang  showed the best physical and mechanical properties with value of MOE and MOR are  8818,34 kg/cm2 and 126,98 kg/cm2.Keywords : biocomposites, alang-alang, polypropylene